2017
DOI: 10.3390/ijgi6090290
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the Best Band Ratio to Estimate Chlorophyll-a Concentration in a Tropical Freshwater Lake Using Sentinel 2A Images from a Case Study of Lake Ba Be (Northern Vietnam)

Abstract: This study aims to develop a method to estimate chlorophyll-a concentration (Chla) in tropical freshwater lake waters using in situ data of Chla, water reflectance, and concurrent Sentinel 2A MSI imagery (S2A) over Lake Ba Be, a Ramsar site and the largest natural freshwater lake in Vietnam. Data from 30 surveyed sampling sites over the lake water in June 2016 and May 2017 demonstrated the appropriateness of S2A green-red band ratio (band 3 versus band 4) for estimating Chla. This was shown through a strong co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 38 publications
9
78
0
14
Order By: Relevance
“…Retrieving the concentration of chlorophyll-a using satelliteremote sensing remains a challenge not only due to the presence of several OAC but also of the available sensors specifications (Ha et al, 2017), particularly in water bodies which are in proximity to the land-based activities. Some studies showed that the broad wavelength spectral data available on current satellites (i.e., Landsat, SPOT) does not allow the estimation of chlorophyll-a in turbid water (Dekker and Peters, 1993;Ha et al, 2017).…”
Section: Blondeaumentioning
confidence: 99%
“…Retrieving the concentration of chlorophyll-a using satelliteremote sensing remains a challenge not only due to the presence of several OAC but also of the available sensors specifications (Ha et al, 2017), particularly in water bodies which are in proximity to the land-based activities. Some studies showed that the broad wavelength spectral data available on current satellites (i.e., Landsat, SPOT) does not allow the estimation of chlorophyll-a in turbid water (Dekker and Peters, 1993;Ha et al, 2017).…”
Section: Blondeaumentioning
confidence: 99%
“…In the 2-BM we used, we obtained a correlation of R 2 = 0.49 and RMSE = 9.97 mg m −3 . In addition, Ha et al [44] obtained 2-BM R 2 values of 0.68 using 560 nm and 665 nm and R 2 =0.29 using 705 nm and 665 nm for Vietnam's Lake Ba Be (Chla range of 1-6 mg m −3 ). This difference indicates the 705-nm and 665-nm frequencies in the 2-BM as more effective in water areas with advanced eutrophication.…”
Section: Feasibilities Of Chla and Turbidity Estimation Using The Senmentioning
confidence: 99%
“…Bao quanh hồ là những dãy núi đá vôi cao từ 570 -893 m với rừng nhiệt đới thường xanh nguyên sinh (Hình 1). Khu vực đặc trưng cho điều kiện khí hậu gió mùa, với sự phân hóa về nhiệt độ, lượng mưa theo mùa hè và mùa đông [10]. Giá trị nhiệt độ có sự chênh lệch lớn giữa mùa hè và mùa đông, với giá trị nhiệt độ thấp nhất và cao nhất lần lượt xảy ra trong tháng 1 và tháng 7.…”
Section: Khu Vực Nghiên Cứuunclassified